BUDGET PARTICIPATION, ORGANIZATIONAL COMMITMENT, JOB RELEVANT INFORMATION AND POTENTIAL INFORMATION ASYMMETRY CAUSE BUDGETING SLACK - Runindita, Kartika (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
In several studies on behavioral accounting, there are dysfunctional behaviors that occur in government agency budget planning cycles. The phenomenon of budgetary slack that often occurs is that employees do not want to work optimally and are even dysfunctional and hide information for their own interests. The causes of budgetary slack lead to agency theory which results in information asymmetry between budget makers (agents) and company owners (principals). The purpose of this study is to discuss factors that have the potential to cause budgetary slack, including budgetary participation, organizational commitment, job relevant information, and information asymmetry. The purpose of this article is to discuss with literature review the factors that have the potential to cause budgetary slack are participative budgeting, organizational commitment, job relevant information and information asymmetry. The results of this study are if budget participation, organizational commitment, job relevant information, and information asymmetry cause budgetary slack. therefore, a clear continuity is needed between the right participatory budgeting, strong organizational commitment, job relevant information, and appropriate information symmetry to prevent budgetary slack.